Cooperative Learning Approach to an English Academic Reading Course - Fuad Hasyim (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
This research aims to get description of Cooperative Learning application using Student Teams Achievement Divisions (STAD) type to improve students’ motivation and independence learning level. The applied research method was classroom action research. The observations have been done during seven cycles to research the subjects; those are students of Basic Academic Reading Class C of 2018/2019 at department of management, faculty of economy, Universitas Islam Indonesia. The result showed that the number of students achieving maximum scores (A) has significantly increased, up to 31% of previous year as the baseline. Meanwhile, the average students’ attendances in entire semester have also increased up to 13% of previous year baseline. The questionnaire was also distributed before and after cycles to measure the changes in students’ perception of their motivation and independent learning level. The result indicated the increase in average score of every aspect in all variables. However, the result of independent sample t-test showed that sig (2-tailed) score of students’ motivation and independence learning level have significant differences. Thus, it is concluded that Cooperative Learning model on Student Teams Achievement Divisions (STAD) type has a positive and significant impact on developing student’s motivation and independent learning level.